Hodgkin's lymphoma with unusual pulmonary presentations: Reporting two cases - Brett Matthew Lowenthal; Xiangdong Xu; Meera Subash; Lily J Jih (Wolters Kluwer Medknow Publications, 2017)
Classical Hodgkin's lymphoma (CHL) presenting with exclusively pulmonary symptoms is very unusual. We report two cases of CHL with atypical clinical presentations mimicking pulmonary infections. The first case represents a stage IV CHL with secondary lung involvement, and the second case demonstrates a very rare case of CHL with isolated lung involvement, also known as primary pulmonary Hodgkin's lymphoma. The second patient was initially misdiagnosed and treated with six months of antibiotics before the correct diagnosis was made by a lung biopsy. Both patients received chemotherapy; one patient achieved complete remission and the other achieved near-complete remission.